Baseline characteristics of idiopathic pulmonary fibrosis: analysis from the Australian Idiopathic Pulmonary Fibrosis Registry. Issue 2 (23rd February 2017) - Jo, Helen E.; Glaspole, Ian; Grainge, Christopher; Goh, Nicole; Hopkins, Peter M.A.; Moodley, Yuben; Reynolds, Paul N.; Chapman, Sally; Walters, E. Haydn; Zappala, Christopher; Allan, Heather; Keir, Gregory J.; et al.
The prevalence of idiopathic pulmonary fibrosis (IPF), a fatal and progressive lung disease, is estimated at 1.25–63 out of 100 000, making large population studies difficult. Recently, the need for large longitudinal registries to study IPF has been recognised. The Australian IPF Registry (AIPFR) is a national registry collating comprehensive longitudinal data of IPF patients across Australia. We explored the characteristics of this IPF cohort and the effect of demographic and physiological parameters and specific management on mortality. Participants in the AIPFR (n=647, mean age 70.9±8.5 years, 67.7% male, median follow up 2 years, range 6 months–4.5 years) displayed a wide range of age, disease severity and co-morbidities that is not present in clinical trial cohorts. The cumulative mortality rate in year one, two, three and four was 5%, 24%, 37% and 44% respectively. Baseline lung function (forced vital capacity, diffusing capacity of the lung for carbon monoxide, composite physiological index) and GAP (gender, age, physiology) stage (hazard ratio 4.64, 95% CI 3.33–6.47, p<0.001) were strong predictors of mortality. Patients receiving anti-fibrotic medications had better survival (hazard ratio 0.56, 95% CI 0.34–0.92, p=0.022) than those not on anti-fibrotic medications, independent of underlying disease severity. The AIPFR provides important insights into the understanding of the natural history and clinical management of IPF. Data from the Australian IPF registry shows anti-fibrotic therapy and baseline physiology predict survival in IPF http://ow.ly/Ete2305OkU9